Evidence brief: Improving access to care and outcomes for heart failure in Ontario - Waddell, K; Moat, KA; Lavis, JN (My University, 2019)
An assessment of what is known about problems related to access to care and outcomes for heart failure, elements of a comprehensive approach for addressing these problems, and key implementation considerations. The evidence brief was an input to a stakeholder dialogue on the topic of improving access to care and outcomes for heart failure in Ontario
Keywords: access; care; heart; failure; Ontario